Wireless, Multifunctional System-Integrated Programmable Soft Robot - Sungkeun Han; Jeong-Woong Shin; Joong Hoon Lee; Bowen Li; Gwan-Jin Ko; Tae-Min Jang; Ankan Dutta; Won Bae Han; Seung Min Yang; Dong-Je Kim; Heeseok Kang; Jun Hyeon Lim; et al. (Nano-Micro Letters)
Highlights A soft, untethered electronic robot that integrates magnetically responsive engineered composites, enabling reversible programming and a diverse range of motions and shapes. Seamless integration of a meticulously designed soft/flexible electronic system with the magnetic soft robot guarantees the stable and accurate execution of multi-modal electrical functions while preserving the integrity of its mechanical movement. The comprehensive demonstration illustrates the feasibility of the untethered, integrated magnetic soft robot, highlighting its stable operation, adaptability, and ability to perform complex tasks under diverse conditions.